2013
DOI: 10.4070/kcj.2013.43.8.527
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recovery of Left Ventricular Systolic Dysfunction after Acute Myocardial Infarction: From the Korean Acute Myocardial Infarction Registry and Korean Myocardial Infarction Registry

Abstract: Background and ObjectivesWe investigated the predictors of the recovery of depressed left ventricular ejection fraction (LVEF) in patients with moderate or severe left ventricular (LV) systolic dysfunction after acute myocardial infarction (MI).Subjects and MethodsWe analyzed 1307 patients, who had moderately or severely depressed LVEF (<45%) on echocardiography soon after acute MI and who underwent a follow-up echocardiography, among 27369 patients from the Korea Working Group on the Myocardial Infarction Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
(26 reference statements)
3
23
3
Order By: Relevance
“…Peak troponin and CK-MB could significantly predict LV functional recovery at 6 months. This finding support previous findings that peak troponin level strongly predicts the recovery of LV function even more important than any other clinical measure (49,50).…”
Section: Prediction Of Reverse Remodeling At 6 Monthssupporting
confidence: 91%
“…Peak troponin and CK-MB could significantly predict LV functional recovery at 6 months. This finding support previous findings that peak troponin level strongly predicts the recovery of LV function even more important than any other clinical measure (49,50).…”
Section: Prediction Of Reverse Remodeling At 6 Monthssupporting
confidence: 91%
“…Systolic function and troponin levels at the time of MI have been shown to have strong associations with subsequent functional recovery (4,6,11). Prior studies have reported an association between BNP elevation and adverse remodeling at 4 months (increase in LV end-diastolic volume by 20%), a finding not repeated in our study (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] This registry was sponsored by the Korean Society of Cardiology and managed by the Korean working group of AMI. Participating centers are mainly academic centers with high volumes of patients, facilities for primary PCI, and on-site cardiac surgery.…”
Section: Study Populationmentioning
confidence: 99%